Concept of corporate reststructuring and reengineering - Tetřevová, Liběna (Univerzita Pardubice, 2007)
The article deals with main concepts of corporate restructuring and reengineering. Firstly, the term restructuring is defined and the concept of corporate restructuring is explained. Secondly, the spheres of corporate restructuring are suggested and discussed. Finally, the term revitalization is cleared and the idea of corporate revitalization is characterized. Attention is paid to relationship between corporate restructuring and reengineering as well.

The article deals with main concepts of corporate restructuring and reengineering. Firstly, the term restructuring is defined and the concept of corporate restructuring is explained. Secondly, the spheres of corporate restructuring are suggested and discussed. Finally, the term revitalization is cleared and the idea of corporate revitalization is characterized. Attention is paid to relationship between corporate restructuring and reengineering as well.
Keywords: restrukturalizace podniku; Reengineering; transformace řízení podniku; Integrace; racionalizace